DEVELOPMENT OF RME BASED MATHEMATICS LEARNING MEDIA TO IMPROVE CONCEPT UNDERSTANDING ABILITY OF ELEMENTARY SCHOOL STUDENTS IN GRADE IV SDN 165728 TEBINGTINGGI - Tri Mariani Manik; Edi Syahputra; Khairil Ansari (Sensei International Journal of Education and Linguistic, 2021)
This study aims to develop learning media software to determine the feasibility and effectiveness of learning media in improving student learning outcomes on KPK and FPB materials. Researchers use the media, namely Video Learning, to design and develop learning media. This type of research is ADDIE development research. The effectiveness of the learning video based on the learning outcomes test, namely on the completeness of the individual learning outcomes data in the class using the learning video, it is stated that all students are complete. Based on the validator's assessment results of the material experts, the feasibility reached 4.45 with a very decent category. The media expert obtained feasibility of 4.35 with a very feasible category, and the design expert obtained feasibility of 4.14 with a decent category. From the validation results, the feasibility of the KPK and FPB learning videos is feasible to use. This proves that learning videos are more effectively used and proven to improve student learning outcomes on KPK and FPB materials in Class IV SDN 165728 Tebingtinggi.